Absence of complementary sex determination in two Leptopilina species (Figitidae, Hymenoptera) and a reconsideration of its incompatibility with endosymbiont‐induced thelytoky. (25th October 2021) - Chen, Fangying; Schenkel, Martijn; Geuverink, Elzemiek; van de Zande, Louis; Beukeboom, Leo W.
Abstract: Complementary sex determination (CSD) is a widespread sex determination mechanism in haplodiploid Hymenoptera. Under CSD, sex is determined by the allelic state of one or multiple CSD loci. Heterozygosity at one or more loci leads to female development, whereas hemizygosity of haploid eggs and homozygosity of diploid eggs results in male development. Sexual (arrhenotokous) reproduction normally yields haploid male and diploid female offspring. Under asexual reproduction (thelytoky), diploidized unfertilized eggs develop into females. Thelytoky is often induced by bacterial endosymbionts that achieve egg diploidization by gamete duplication. As gamete duplication leads to complete homozygosity, endosymbiont‐induced thelytokous reproduction is presumed to be incompatible with CSD, which relies on heterozygosity for female development. Previously, we excluded CSD in four Asobara (Braconidae) species and proposed a two‐step mechanism for Wolbachia‐ induced thelytoky in Asobara japonica . Here, we conclusively reject CSD in two cynipid wasp species, Leptopilina heterotoma and Leptopilina clavipes . We further show that thelytoky in L. clavipes depends on Wolbachia titer but that diploidization and feminization steps cannot be separated, unlike in A. japonica . We discuss what these results reveal about the sex determination mechanism of L. clavipes and the presumed incompatibility between CSD and endosymbiont‐induced thelytoky in the Hymenoptera. Abstract : Under complementary sex determination (CSD), if the fertilized eggs are homozygous, they develop into diploid males. Forms of thelytoky induced by endosymbiont lead to genome homozygosity as well. By presenting our results in two cynipid wasp species Leptopilina heterotoma and Leptopilina clavipes, we discuss the presumed incompatibility between CSD and endosymbiont‐induced thelytoky in Hymenoptera.